A new offer ofNTRUcryptosystem with two new key pairs - ÖZDEMİR, AHMET ŞÜKRÜ (WILEY, 2021)
In this study, it is aimed to contribute to the NTRU cryptologic system to increase the number of operations of taking module by taking a polynomial module, to increase the number of secret key by adding an isomorphism and also to increase the number of public key by choosing an irreducible polynomial. Since it is calculated module by suitably partitioning a chosen message polynomial, and since it is used properties of module being an algebraic structure in a phase of an operation and a decryption by adding to the system prime number module and prime polynomial module, this title is thought fit.
Keywords: cryptosystem; decryption; encryption; module; NTRU